(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
The nutritional composition and antinutritional factors of Rhynchosia bracteata Benth. underexploited tribal pulses locally known as Advi Chekkudu in Telugu, used as food by local tribals in the Rollapenta forest, Kurnool district, Nallamalais of Andhra Pradesh. The mature seed samples were analysed for proximate composition, total (true) seed protein fractions, amino acid composition, fatty acids profile, mineral and antinutritional factors. The investigated seed samples contained higher amount of crude protein, crude fat, ash and nitrogen free extractives constitute 20.18, 6.16, 6.12 and 61.31 % respectively. The calorific value of the seed weight 100 g dry seed material was 366.86 K.cal. The essential amino acids, leucine, tyrosine and phenylalanine, were present in relatively large quantities. The fatty acid profiles revealed that the seed lipids contained higher concentrations of palmitic and linoleic acids. The seeds are rich in magnesium, iron potassium and phosphorous. Antinutritional factors such as total free phenols, (3.76 %) tannins (0.29%), L -DOPA (0.51%), hydrogen cyanide (0.066%) and phytic acid (0.18%) are present in variable quantities. This paper presents the chemical composition and nutritional potential of Rhynchosia bracteata seeds with regard to its suitability as a regular component in human diet. Key words. Rhynchosia bracteata; Proximate composition; Amino acids; Antinutritional factors; Fatty acids; Protein fractions; Hemagglutinating activity DOI: http://dx.doi.org/10.3329/bjsir.v46i2.4488 Bangladesh J. Sci. Ind. Res. 46(2), 141-146, 2011